Golgi- and Trans-Golgi Network-Mediated Vesicle Trafficking Is Required for Wax Secretion from Epidermal Cells . Issue 3 (27th January 2014) - McFarlane, Heather E.; Watanabe, Yoichiro; Yang, Weili; Huang, Yan; Ohlrogge, John; Samuels, A. Lacey
Abstract : Plant epidermal cells, which produce large amounts of protective lipids, rely on vesicle traffic to export these wax molecules to the cuticle . Abstract: Lipid secretion from epidermal cells to the plant surface is essential to create the protective plant cuticle. Cuticular waxes are unusual secretory products, consisting of a variety of highly hydrophobic compounds including saturated very-long-chain alkanes, ketones, and alcohols. These compounds are synthesized in the endoplasmic reticulum (ER ) but must be trafficked to the plasma membrane for export by ATP-binding cassette transporters. To test the hypothesis that wax components are trafficked via the endomembrane system and packaged in Golgi-derived secretory vesicles, Arabidopsis ( Arabidopsis thaliana ) stem wax secretion was assayed in a series of vesicle-trafficking mutants, including gnom like1-1 ( gnl1-1 ), transport particle protein subunit120-4, and echidna ( ech ). Wax secretion was dependent upon GNL1 and ECH. Independent of secretion phenotypes, mutants with altered ER morphology also had decreased wax biosynthesis phenotypes, implying that the biosynthetic capacity of the ER is closely related to its structure. These results provide genetic evidence that wax export requires GNL1- and ECH-dependent endomembrane vesicle trafficking to deliver cargo to plasma membrane-localized ATP-binding cassette transporters.